Distributional overlap and potential competition between a threatened habitat specialist and generalist frog species in coastal wallum habitats of South East Queensland, Australia. (2nd September 2022) - Filer, Alannah; Meyer, Edward A.; van Rensburg, Berndt J.
Abstract: Coastal wallum wetlands inhabited by the vulnerable wallum sedgefrog ( Litoria olongburensis ) are highly susceptible to habitat degradation owing to their unusual hydrology and water chemistry. Anthropogenic impacts on wallum wetland environs pose a significant threat to the wallum sedgefrog by allowing the eastern sedgefrog ( Litoria fallax ), a habitat generalist and closely related competitor species, to colonise and displace the wallum sedgefrog from disturbed wallum habitat. To identify 'at risk' areas, overlapping species distribution models were utilised to highlight areas of sympatry between these species in south east Queensland, where competition with the eastern sedgefrog poses a particular threat to the wallum sedgefrog. Significant areas of distributional overlap (including 47% of the wallum sedgefrog's modelled distribution) were identified, primarily in mainland areas where anthropogenic disturbance is highest. When overlayed with the boundaries of protected areas, 84% of the area exclusively inhabited by the wallum sedgefrog occurs within the bounds of protected lands. In contrast, 74% of overlapping distribution of the two species occurred outside of these parks, highlighting the importance of protected areas in the conservation of the wallum sedgefrog. This study highlights areas where competition with the eastern sedgefrog presents a particular threat to the wallum sedgefrog, helping inform effective conservation initiatives for this species.